Integrated management of leaf blight of Isabgol caused by Alternaria alternata - and B. UPAYDHYAY, RAJESH KUMAR MEENA*, S.S. SHARMA (Indian Phytopathology, 2014)
The experiments were conducted at Department of Plant Pathology, Rajasthan College of Agriculture, Udaipur, in Rajasthan. Alternaria alternata was isolated from leaves of Isabgol and observed to be pathogenic under artificial conditions. Various fungicides, plants extracts and varietal screening were tested against the fungus. Among five fungicides Mancozeb was found most effective against Alternaria alternata in vitro and in vivo conditions followed by Copper oxychloride and Zineb. Relative efficacy of five plants extracts viz., Azadirachta indica, Allium sativum, Datura stramonium, Argemone maxicana and Lantana camara in different concentrations were studied by poisoned food technique. Among the five plant extracts, Allium sativam was found most effective followed by Neem leaves (Azadirachta indica). In general, higher concentrations of plant extract were more effective in reducing mycelial growth and sporulation as compared to lower concentrations. Among ten cultivars MIB-125, PB-7 and PB-62 showed moderate resistance to blight disease and local Isabgol variety gave high susceptible reaction to blight disease where none of cultivar was found completely free from disease.